Kepentingan India di Togo : Implementasi Scaling Solar Rooftop - Vandayani, Kadek Sri; Sushanti, Sukma; Putri, Penny Kurnia (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL), 2023)
This research aims to determine India's interest in providing funding to Togo in the solar rooftop scaling program through LoC.  Scaling solar rooftop is one of the programs owned by ISA, an alliance of countries which are prosperous in solar resources. This research uses a descriptive qualitative method and draws upon the concept of national interest and grand strategy. This research finds that the provision of LoC in the solar rooftop scaling program was based on the economic interests of India to be accomplished in Togo. India has an interest in increasing exports to Togo through points of agreement providing LoC in which points of the agreement are agreed upon points of agreement that can increase India's exports. Based on this point, India's exports to Togo will increase, this increase has an impact on improving the economy which is in India's interest.